A case of secondary syphilis with pulmonary involvement and review of the literature. (September 2018) - Visuttichaikit, Suttichai; Suwantarat, Nuntra; Apisarnthanarak, Anucha; Damronglerd, Pansachee
Syphilis is a sexually transmitted systemic infection caused by Treponema pallidum . We report a case of a heterosexual, HIV-positive man who presented with secondary syphilis and a lung abscess. A bacterial lung abscess was suspected and a computed tomography-guided percutaneous needle aspiration of the lung abscess was performed. Direct pulmonary involvement by T. pallidum was suggested by a positive PCR result on the aspirated fluid specimen. The clinical signs of secondary syphilis improved, and the lung abscess was resolved after treatment with benzathine penicillin G and amoxicillin-clavulanate. The final diagnosis was secondary pulmonary syphilis. Few reports of secondary syphilis with pulmonary involvement have been reported to date.